Actions to Perfect Integrating Evaluation in The Training Of Physical Education Teachers - Isaac Alejandro Aquino , Davila; Gerardo Joel Arredondo , Martell; Gustavo Álvarez , Mendoza; Antonio Ornelas , Gracián (European Scientific Journal, ESJ, 2021)
Experience is shared in the application of actions aimed at improving the training of physical educators. It also highlights the evaluation as a substantial element in the training of the professional of physical culture at the Universidad Autónoma de Chihuahua, Mexico. It takes the evaluation as a didactic category that allows integrating all the elements of the teaching-learning process and in its application to verify the effectiveness of the training process. This paper focuses on the elaboration of didactic actions to improve the professional performance of the Physical Culture of students through evaluations in real contexts. Methodologically, collaborative research was used as a variant of participatory action research and as a case study method. As a significant result, it was possible to elaborate and apply the actions to improve the integrative evaluation, which allows evaluating the integration of all the didactic elements in terms of practical performance.